Miniaturized high-throughput synthesis and screening of responsive hydrogels using nanoliter compartments. (March 2020) - Rosenfeld, Alisa; Oelschlaeger, Claude; Thelen, Richard; Heissler, Stefan; Levkin, Pavel A.
Abstract: The traditional pipeline of hydrogel development includes individual one-by-one synthesis and characterization of hydrogels. This approach is associated with the disadvantages of low-throughput and high cost. As an alternative approach to classical one-by-one synthesis, high-throughput development of hydrogels is still tremendously under-represented in the field of responsive material development, despite the urgent requirement for such techniques. Here, we report a platform that combines highly miniaturized hydrogel synthesis with screening for responsive properties in a high-throughput manner. The platform comprises a standard glass slide patterned with 1 ​× ​1 ​mm hydrophilic regions separated by superhydrophobic liquid-impermeable barriers, thus allowing deposition of various precursor solutions onto the hydrophilic spots without cross-contamination. The confinement of these solutions provided by the hydrophilic/superhydrophobic pattern allows encapsulation of cells within the hydrogel, and enables variation in hydrogel height and width. We have also proved the proper mixing of chemicals within the nanoliter-sized droplets. We have successfully implemented this platform for the synthesis of hydrogels, constructing 53 unique hydrogels, to demonstrate the versatility and utility of the platform. Photodegradation studies were performed on 20 hydrogels, revealing structure/function relationships between the hydrogel composition and photodegradability, and covering the range of degradability from non-degradable to rapidly degradable materials. Graphical abstract: In order to discover and optimize stimuli-responsive materials fast, miniaturized high-throughput methodologies should be utilized. Herein, a droplet microarray platform for a nanoliter-scale high-throughput combinatorial hydrogel synthesis is demonstrated. The platform comprises hundreds of hydrophilic spots, serving as separate reaction microreservoirs, surrounded by superhydrophobic borders. Several libraries of photodegradable hydrogels are synthesized, covering the range of degradability from non-degradable to rapidly degradable materials. Image 1